Ultra-Thin Chiral Metasurface-Based Superoscillatory Lens - Li, Jinxing; Yang, Guohui; Yuan, Yueyi; Wu, Qun; Zhang, Kuang (Frontiers in Materials, 2022)
The metasurface-based superoscillatory lens has been demonstrated to be effective in finely tailoring the wavefront of light to generate focal spots beyond the diffraction limit in the far-field that is capable of improving the resolution of the imaging system. In this paper, an ultra-thin (0.055 λ0) metasurface-based superoscillatory lens (SOL) that can generate a sub-diffraction optical needle with a long focal depth is proposed, which is constructed by ultra-thin chiral unit cells containing two metal split-ring resonators (SRR) with a 90° twisted angle difference cladded on both sides of a 1.5 mm-thick dielectric substrate, with a high linear cross-polarized transmission coefficient around 0.9 and full phase control capability at 11 GHz. Full-wave simulation shows that SOL generates a sub-diffraction optical needle within 10.5–11.5 GHz. At the center frequency, the focal depth is 281 mm (10.3 λ0) within 105–386 mm, the full width at half maximum (FWHM) is 18.5 mm (0.68 λ0), about 0.7 times the diffraction limit, generally consistent with the theoretical result. The proposed ultra-thin chiral metasurface-based SOL holds great potential in integrating into practical imaging applications for its simple fabrication, high efficiency, and low-profile advantages.